2013
DOI: 10.1186/1471-2482-13-s2-s41
|View full text |Cite
|
Sign up to set email alerts
|

Cytological diagnosis of thyroid nodules in Hashimoto thyroiditis in elderly patients

Abstract: BackgroundLong standing Hashimoto Thyroiditis (HT) causes shrinking and atrophy of the thyroid, but may also lead to diffuse enlargement of the gland and/or formation of nodules. These nodules should be differentiated from papillary thyroid carcinoma (PTC) and primary thyroidal non-Hodgkin lymphoma (PTL), which are possible complications of HT, and require pre-surgical diagnoses and different treatments.This study focuses on the role of fine-needle cytology (FNC) in the clinical surveillance and pre-surgical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Patients with Hashimoto's thyroiditis(−) and BRAF V600E mutation(+) were more likely to develop poor prognosis. Fine‐needle aspiration biopsy is recommended to evaluate the condition of thyroid nodules preoperatively; results of several studies have shown that Hashimoto's thyroiditis and BRAF V600E mutation have relatively high sensitivity and specificity . Therefore, preoperative information of Hashimoto's thyroiditis and BRAF V600E mutation by fine‐needle aspiration biopsy can be utilized in practice and help surgeons predict clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Hashimoto's thyroiditis(−) and BRAF V600E mutation(+) were more likely to develop poor prognosis. Fine‐needle aspiration biopsy is recommended to evaluate the condition of thyroid nodules preoperatively; results of several studies have shown that Hashimoto's thyroiditis and BRAF V600E mutation have relatively high sensitivity and specificity . Therefore, preoperative information of Hashimoto's thyroiditis and BRAF V600E mutation by fine‐needle aspiration biopsy can be utilized in practice and help surgeons predict clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The nonspecific ultrasonographic findings seen in HT complicate follow-up by making it more difficult to assess tumor size or identify other areas of concern within the thyroid both at presentation and during follow-up (28,29). Furthermore, HT often leads to atypical cervical lymphadenopathy (30), which makes it more difficult to exclude locoregional metastasis confidently.…”
Section: Rationale For Classification As An Appropriate Candidate Formentioning
confidence: 99%
“…These AVMs increase in size during pregnancy [3]. The differential diagnosis was for: abnormal systemic vessels, highly vascular parenchymal mass, other congenital or acquired pulmonary arterial or venous lesions (e.g pulmonary varix), retroperitoneal varices [11,16,2132]. …”
Section: Discussionmentioning
confidence: 99%